Supply Chain Strategies for Electronic Component Base in Industrial Enterprises - Litvin, Alexander (Scientific Journal of Bielsko-Biala School of Finance and Law, 2025)
The paper examines supply chain strategies of the electronic components base in industrial enterprises in Germany, Poland, Spain, and China between 2020 and 2024. The research is of strong relevance as a result of ongoing global disruptions, semiconductor scarcities, and the digitalization of industrial networks which is currently in rapid progress. The goal is to determine the operational performance and resilience consequences of multi-sourcing, collaborating with suppliers, nearshoring, and digital traceability. A quantitative, comparative research method was used which relied on secondary data in 280 firms followed over five years. The methodology is a combination of descriptive statistics and econometric modelling, such as two-way fixed effects, moderation, mediation and instrumental variable estimation to account for endogeneity. The results reveal that digital traceability (β₆ = 0.211-0.236) and supplier collaboration (β₅ = 0.129-0.173) have the most significant positive effects on operational performance, and supplier concentration (HHI) is a negative determinant (or negative influence) (-0.115 to -0.189). Germany and China have made the largest improvements on service level (from 87-88% to 94%) and lead-time volatility (down 23-25%), while Poland and Spain showed steady but moderate improvement.